Template-based orientation control of nanoparticles toward mechanically reinforced polypropylene/silica nanocomposites. (5th January 2023) - Chammingkwan, Patchanee; Takeuchi, Kengo; Wada, Toru; Terano, Minoru; Taniike, Toshiaki
Abstract: Design of nanocomposites at a nanometer scale by controlling the orientation of fillers can lead to substantial improvement in properties. In this study, biaxially oriented PP (BOPP) was exploited for templating control the growth and orientation of nanoparticles. Silicon alkoxide was impregnated in the amorphous space of BOPP using supercritical CO2 -assisted impregnation. The subsequent sol-gel reaction led to the in-situ formation of highly dispersed silica nanoparticles. Restriction of the particle growth by the confined amorphous space in BOPP induced the formation of anisotropic particles. We showed that the synergistic contribution of the formation of anisotropic particles with preferential orientation and the crystalline orientation of the matrix brought dramatic enhancement in the reinforcement. Graphical abstract: Image 1